2020
DOI: 10.24912/jmstkik.v4i2.7892
|View full text |Cite
|
Sign up to set email alerts
|

Rencana Sabuk Hijau Timur Kotabaru Kebayoran: Kebijakan Setengah Hati? Studi Tentang Transformasi Kawasan

Abstract: Kebayoran new city was the first satellite city planned on the outskirts of post-world war II Jakarta. By applying the garden city concept, Kebayoran new city was planned to have green belt elements in the west and east to limit its growth. Along with the rapid development of the main axis of the City of Jakarta (Jl. Thamrin - Jl. Sudirman) after the transfer of sovereignty (1949) and the expansion of the administrative boundaries of the City of Jakarta, the newcity of Kebayoran has undergone a transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2500) tried to resist but were warned by the authorities that "… if they refuse to move with due compensation they will be evicted with force without any compensation". However, the study byClaudio and Fahmi (2020) has demonstrated that, at least the zone planned for eastern greenbelt, was not fully acquired; up to the 1950s when part of the zone was decided as relocation site of ex-inhabitants of PTIK (Police Education Institute) Complex it was fully occupied by indigenous Jakartans (Betawi). Perhaps, due to this and other challenges JP.…”
mentioning
confidence: 99%
“…2500) tried to resist but were warned by the authorities that "… if they refuse to move with due compensation they will be evicted with force without any compensation". However, the study byClaudio and Fahmi (2020) has demonstrated that, at least the zone planned for eastern greenbelt, was not fully acquired; up to the 1950s when part of the zone was decided as relocation site of ex-inhabitants of PTIK (Police Education Institute) Complex it was fully occupied by indigenous Jakartans (Betawi). Perhaps, due to this and other challenges JP.…”
mentioning
confidence: 99%